USING PICTURES AND GUIDED QUESTIONS TO IMPROVE STUDENTS’ ABILITY IN WRITING DESCRIPTIVE TEXT - Utami Ratna Swari (Ed-Humanistics : Jurnal Ilmu Pendidikan, 2020)
This research is classroom action research. It is carried out at 3rd semester students PGSD study program in Panca Marga University Probolinggo, consisting of 32 students. The objective of the research is to find out how can pictures and guided questions be implemented to improve students’ ability in writing descriptive text. This research is conducted in 2 (two) cycles. The procedure of the research consist of: preliminary study, planning, action, observation, and reflection. Qualitative data are obtained from observation checklist, field notes and interview. While quantitative data are gained from the product of students’ descriptive text writing. The result of the research shows that using picture and guided questions can improve students’ ability in writing descriptive text. As the indicator of success, the researcher adapted scoring rubric consisting 4 level: Level 1 = Very Poor, Level 2 = Fair to Poor, Level 3 = Good to Average, and Level 4 = Excellent to Very Good. It is considered success if 63 % or more than 63% students have reached level 3. In preliminary study only 28% students belongs to level 3. In cycle 1 there a slight significant showing percentage improvement in level 3 (47% students reached level 3). In second cycle, the result of students’ writing finally shows a high improvement, 69% students have reached level 3. It indicates that using picture and guided questions can improve students’ ability in writing descriptive text. Keywords: picture, guided questions, writing, descriptive text